Manganese sulfide enables the formation of a highly active β-MnOOH electrocatalyst for effective alkaline water oxidation. (June 2022) - Walter, C.; Kalra, S.; Beltrán-Suito, R.; Schwarze, M.; Menezes, P.W.; Driess, M.
Abstract: Inspired by the manganese (Mn)-containing oxygen-evolving complex of photosystem II, large efforts have been made in the last few years to develop efficient artificial Mn-based catalysts for water oxidation but with limited success. Most of such Mn-based electrocatalysts are merely precatalysts and form MnOx structures as active phases under electrocatalytic conditions. The current focus includes the advancement of synthetic methods to produce solid-state MnOx catalysts of controllable shape, size, composition, and electronic structure. We now learned that using the new hexakis(pyridiniumsulfido) Mn II complex 1, [Mn(pyHS)6 ](OTf)2, as a molecular precursor furnishes cubic-shaped manganese sulfide nanostructures under hot-injection conditions. The latter were electrophoretically deposited on different electrode substrates and found to undergo unexpected transformation to crystalline β-MnOOH with surface stabilized Mn III sites under alkaline water oxidation conditions instead of forming previously known active layered birnessite δ-MnO2 phase. This anomalously active β-MnOOH material outperforms recently reported MnOx -based catalysts for water oxidation under identical reaction conditions. Highlights: A novel molecular manganese complex has been synthesized and used to produce nanostructured manganese sulfide (MnS). The catalytic oxygen evolution reaction of MnS electrode in alkaline media has been investigated showing promising activity. A combination of microscopic, spectroscopic, and analytical techniques has been used to uncover the active structure. Transformation of MnS into an unprecedented highly active β-MnOOH with surface stabilized Mn III sites as the real active catalyst.